2021
DOI: 10.3390/polym13020244
|View full text |Cite
|
Sign up to set email alerts
|

The Quantitative Nanomechanical Mapping of Starch/Kaolin Film Surfaces by Peak Force AFM

Abstract: Starch films modified with additives are materials increasingly being used in the production of packaging. These types of biopolymers can, to a considerable degree, replace plastic, contributing to the reduction in both production and waste management costs. However, they should be characterised by specific mechanical and surface parameters which determine their application. In the presented work, the PeakForce Quantitative Nanomechanics Mapping (PFQNM) method was applied to analyse a starch-based biopolymer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…In this sense, it has been observed that some nano-sized additives added at low concentrations can generate significant improvements in the mechanical, thermal, optical, and physicochemical properties of the materials compared to the pure biopolymer, all this without compromising their biodegradability. The use of reinforcing materials with nanometric particle sizes favors a more homogeneous dispersion of these, increasing the specific surface of reinforcements such as nano cellulose and nanoclays; these materials also exhibit improved thermal, mechanical, and barrier properties when reinforcing concentrations used are lower (1-5% by volume) than when using micrometer size or larger reinforcements [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, it has been observed that some nano-sized additives added at low concentrations can generate significant improvements in the mechanical, thermal, optical, and physicochemical properties of the materials compared to the pure biopolymer, all this without compromising their biodegradability. The use of reinforcing materials with nanometric particle sizes favors a more homogeneous dispersion of these, increasing the specific surface of reinforcements such as nano cellulose and nanoclays; these materials also exhibit improved thermal, mechanical, and barrier properties when reinforcing concentrations used are lower (1-5% by volume) than when using micrometer size or larger reinforcements [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the surface morphology of SN x crystals in nm scale, AFM with various modes such as PeakForce Quantitative Nanomechanics (PF‐QNM) and standard tapping has been performed. [ 27–32 ] Figure shows AFM height images taken in PF‐QNM mode in two different sizes. The images depict the fibrillar nature of the SN x crystal with various fiber diameters in the range of about 50 to 100 nm.…”
Section: Resultsmentioning
confidence: 99%
“…A digital resolution of 512 px × 512 px and a scanning rate of 0.5 Hz were used, and the z-range was set at 300 nm. The Young's modulus was determined by fitting a linearized Derjaguin-Muller-Toporov (DMT) model to the contact part of the retraction curve [24,25]. Additionally, the adhesion force, identified by the attraction between the AFM tip and the sample surface, was determined.…”
Section: Surface Properties 241 Atomic Force Microscopymentioning
confidence: 99%